How to communicate with patients about future illness progression and end of life: a systematic review - Parry, Ruth; Land, Victoria; Seymour, Jane (BMJ Publishing Group, 2014)
Background: Conversation and discourse analytic research has yielded important evidence about skills needed for effective, sensitive communication with patients about illness progression and end of life. Objectives To: Locate and synthesise observational evidence about how people communicate about sensitive future matters; Inform practice and policy on how to provide opportunities for talk about these matters; Identify evidence gaps. Design: Systematic review of conversation/ discourse analytic studies of recorded interactions in English, using a bespoke appraisal approach and aggregative synthesis. Results: 19 publications met the inclusion criteria. We summarised findings in terms of eight practices: fishing questions - open questions seeking patients’ perspectives (5/19); indirect references to difficult topics (6/19); linking to what a patient has already said — or noticeably not said (7/19); hypothetical questions (12/19); framing difficult matters as universal or general (4/19); conveying sensitivity via means other than words, for example, hesitancy, touch (4/19); encouraging further talk using means other than words, for example, long silences (2/19); and steering talk from difficult/negative to more optimistic aspects (3/19). Conclusions: Practices vary in how strongly they encourage patients to engage in talk about matters such as illness progression and dying. Fishing questions and indirect talk make it particularly easy to avoid engaging — this may be appropriate in some circumstances. Hypothetical questions are more effective in encouraging on- topic talk, as is linking questions to patients’ cues. Shifting towards more ‘optimistic’ aspects helps maintain hope but closes off further talk about difficulties: practitioners may want to delay doing so. There are substantial gaps in evidence.